Better nutrition, healthier mind? Experimental evidence from primary schools in rural northwestern China - Xiao-yue LIU; Qi-ran ZHAO; Qi-hui CHEN (Journal of Integrative Agriculture, 2019)
Malnutrition and mental health problems are both prevalent among rural students in China. To provide a better understanding of the functional linkage between these two problems, this study estimates the causal effect of improved nutrition on rural students' mental health status, exploiting a randomized controlled trial involving 6044 fourth and fifth graders in rural northwestern China. Estimation results show that a nutrition subsidy provided by the project significantly improved students' mental health status (measured by their anxiety scale). However, an add-on incentive provided to school principals, which was tied to anemia reduction, almost entirely offset the beneficial impact of the nutrition subsidy. These findings suggest that to improve students' mental health in rural China, not only direct subsidies, such as low-priced school meals, but also correct incentives, especially those tied closely to students' mental health outcomes, should be provided.